The culprit behind amyloid beta peptide related neurotoxicity in Alzheimer's disease: oligomer size or conformation? - Broersen, Kerensa (BioMed Central, 2010)
Since the reformulation of the amyloid cascade hypothesis to focus on oligomeric aggregates of amyloid beta as the prime toxic species causing Alzheimer's disease, many researchers refocused on detecting a specific molecular assembly of defined size thatis the main trigger of Alzheimer's disease. The result has been the identification of a host of molecular assemblies containing from two up to a hundred molecules of the amyloid beta peptide, which were all found to impair memory formation in mice. This clearly demonstrates that size is insufficient to define toxicity and peptide conformation has to be taken into account. In this review we discuss the interplay between oligomer size and peptide conformation as the key determinants of the neurotoxicity of the amyloid beta peptide.